Paul, Pagans and Eschatological Ethnicities: A Response to Denys McDonald. (September 2022) - Fredriksen, Paula
An invited response to Denys McDonald's JSNT essay: '"Ex-Pagan Pagans"? Paul, Philo, and Gentile Ethnic Reconfiguration'.